Kebijakan Spin-off dan Efisiensi Perbankan Syariah di Indonesia - Pambuko, Zulfikar Bagus (Universitas Ahmad Dahlan, 2019)
The study aims to analyse the spin-off policies’ impact on the Islamic banks’ efficiency in Indonesia. The study was conducted on five spin-off Islamic banks and efficiency were measured by the BOPO ratio. The research variables used were dummy spin-off, ROA, FDR, and economic growth. Data analysis used panel data regression on annual data from 2008 to 2018. The results suggest that, first, the implementation of spin-off policy significantly increased the operational efficiency of Islamic banking. Second, ROA also has a negative effect on efficiency. Third, FDR and economic growth have no significant effect on the Islamic banks’ efficiency in Indonesia.